Sensitivity analysis of hydraulic properties of naturally fractured reservoirs - Assis, H. B. [UNESP]; Cleto, P. R. [UNESP]; Rodrigues, R. A. [UNESP]; Manzoli, O. L. [UNESP]; Nogueira, C. G. [UNESP] (My University, 2020)
This work aims to apply a sensitivity analysis to determine the influence of natural fractures in a cross section of rock reservoir cell, assessing the equivalent permeability of the medium. Using finite elements with high aspect ratio to represent explicitly the fractures, a single- phase hydraulic problem was evaluated. A fractional factorial design was proposed, in order to avoid the full factorial design, which would require an unviable number of experimental runs. Linear regressions and hypothesis tests were performed to identify the most influential fractures. Second order response surfaces were constructed to estimate the response variable, considering only the most important the fractures. A numerical example is presented, which allows concluding that the most influential fractures are those that cross completely the section along its height, especially those that have greater aperture. In addition, there are some fractures that can be disregard into the discrete fractures models, reducing considerably the computational costs involved on hydraulic simulations of petroleum industry.
Keywords: Discrete fracture model; Elements with high aspect ratio; Natural fractures; Rock permeability; Sensitivity analysis